The namesake : a Commissario Alec Blume novel - Fitzgerald, Conor (Fitzgerald, Conor. Commissario Alec Blume novel., 2012)
Confronted with a murder outside Rome's Piazzo Clodio where the killer has left taunting messages about another unsolved case, Commissioner Alec Blume passes the too-personal investigation to his partner while he attempts to lure an arrogant mafioso out of hiding.